Sosialisasi Kebijakan Pelaksanaan Akreditasi Sekolah dan Madrasah bagi Kepala Sekolah dan Pengawas di Barito Selatan - Rita Rahmaniati; Bulkani Bulkani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
There is a paradigm shift in the assessment of school/madrasah accreditation from an administration-based assessment (compliance) to a performance-based evaluation or rule to principles. AISP-2020 was developed with an emphasis on evaluating four assessment components, namely Graduate Quality, Learning Process, Teacher Quality, and School/Madrasah Management. The existence of these changes requires schools that will be the targets of accreditation need to understand the new instrument. This community service aims to provide insight and increase understanding of the 2020 IASP for school principals and supervisors. This service activity was carried out well and ran smoothly according to the previously planned plan. Socialization participants can understand IASP-2020 through test activities by filling out performance achievements with an accreditation simulation model. Thus this training can increase the knowledge and understanding of school principals and supervisors in South Barito Regency.